KAJIAN PENURUNAN ION (Cl-, SO42-, HCO3-) DALAM AIR LAUT DENGAN RESIN DOWEX - Caecilia Pujiastuti (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Salt is one importance requirement in the daily life, which is the basic commodity is seawater (brine). According to the quality aspect, domestic product especially for consumption requirement has not fulfilled the regulation for healthy yet, especially the one produced by salt farmer. Sea water (brine) is held in the influent reservoir then pumped to the stabilizer tank, accommodated in the reservoir, finally flowed to the resin column. In this column used 1000 grams type-1 Dowex strong acid cation resin. The OH- ion in this resin can be used to tie Cl-, SO4-2 and HCO3- ions on the sea water (brine). Seawater (brine) is out from resin column is accommodated in the influent reservoir, taken every hour during five hour, and then the result obtained analyzed. Variable is operated in this research is contact time of sea water (brine) with resin and current velocity. The best result decreasing content of Cl- occur on the 25 litres/hour current velocity, after five hour it was obtained 1,450% with selectivity coefficient -2,940. Decreasing content of SO4-2 occur on the 10 litters/hour current velocity, in the end, it was obtained 7,267261% with selectivity coefficient -4,745. While decreasing contend of HCO3- occur on the 15 litres/ hour current velocity, later than five hour it was obtained 39,92056% with selectivity coefficient -2,373.